Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
The differential equation governing the velocity v of a falling mass m subject to air resistance...?
proportional to the instantaneous velocity is:
m*dv/dt = mg - kv
where k is a positive constant of proportionality.
a) Solve the equation subject to the initial condition v(0)=A (a constant)
b) Determine the limiting, or terminal, velocity of the weight.
c) if the distance, s, is related to the velocity ds/dt = v, find an explicit expression s if it is further known that s(0)=B (a constant)
Can anyone help? I've been stuck on this problem for a while...
2 Answers
- kbLv 78 years agoFavorite Answer
a) Rewrite in standard form (for a first order linear DE):
m dv/dt + kv = mg
==> dv/dt + (k/m)v = g
Multiply both sides by the integrating factor e^(kt/m):
e^(kt/m) dv/dt + (k/m) e^(kt/m)v = ge^(kt/m)
==> (d/dt) [e^(kt/m) v] = ge^(kt/m), by the product rule.
Integrate both sides:
e^(kt/m) v = (mg/k) e^(kt/m) + C
==> v(t) = mg/k + Ce^(-kt/m).
Find C via v(0) = A:
A = mg/k + C * 1 ==> C = A - mg/k.
Hence, v(t) = mg/k + (A - mg/k) e^(-kt/m).
----------------
b) Let t→∞ with the result from (a):
lim(t→∞) [mg/k + (A - mg/k) e^(-kt/m)] = mg/k + (A - mg/k) * 0 = mg/k.
----------------
c) Integrate the result from (a):
s(t) = mgt/k + (A - mg/k) * (-m/k)e^(-kt/m) + C
We find C by using s(0) = B:
B = 0 + (A - mg/k) * (-m/k) * 1 + C
==> C = B + (A - mg/k) * (m/k).
Hence, s(t) = mgt/k + (A - mg/k) * (-m/k)e^(-kt/m) + [B + (A - mg/k) * (m/k)].
I hope this helps!
- ?Lv 68 years ago
some hints for you
m*dv/dt = mg - kv
dv/dt = g - kv / m
take the anti - derivative with respect to v
v = gt - kvt / m + A
where A is a constant
v + kvt / m = gt + A
v(1 + kt / m) = gt + A
v = (gt + A) / (1 + kt / m)
s = Integral[(gt + A) / (1 + kt / m) dt]
s = m((Ak - gm)ln(kt + m) + gkt) / k^2 + constant